Effect of Tityus serrulatus venom on cytokine production and the activity of murine macrophages - Vera L. Petricevich (Mediators of Inflammation)
The purpose of this study was to investigate the effects of Tityus serrulatus venom (TSV) on murine peritoneal macrophages evaluated in terms of activation. The effects of crude TSV were analysed by detection of cytokines, oxygen intermediate metabolites (H2O2) and nitric oxide (NO) in supernatants of peritoneal macrophages. Several functional bioassays were employed including an in vitro model for envenomating: cytotoxicity of TSV was assessed using the lyses percentage. Tumor necrosis factor (TNF) activity was assayed by measuring its cytotoxic activity on L-929 cells, and interleukin-6 (IL-6) and interferon-γ (IFN-γ) were assayed by enzyme-linked immunosorbent assay, whereas NO levels were detected by Griess colorimetric reactions in culture supernatant of macrophages incubated with TSV and subsequently exposed to either lipopolysaccharide or IFN-γ. Incubation of macrophages with TSV increased production of IL-6 and IFN-γ in a dose-dependent manner. TNF production was not detected in supernatants treated with TSV at any concentration. The increase in IL-6 secretion was not associated with concentration-dependent cytoxicity of TSV on these cells. These data suggest that the cytotoxicity does not appear to be the main cause of an increased cytokine production by these cells. Although NO is an important effector molecule in macrophage microbicidal activity, the inducing potential of the test compounds for its release was found to be very moderate, ranging from 125 to 800 mM. Interestingly, NO levels of peritoneal macrophages were increased after IFN-γ. Moreover, NO production had an apparent effect on macrophage activity. The results obtained here also shown that the TSV induces an important elevation in H2O2 release. These results combined with NO production suggest that TSV possesses significant immunomodulatory activities capable of stimulating immune functions in vitro.